Rates of complete diagnostic testing for patients with acute myeloid leukemia. (26th January 2015) - Lin, Tara L.; Williams, Travis; He, Jianghua; Aljitawi, Omar S.; Ganguly, Siddhartha; Abhyankar, Sunil; Fleming, Allan; Male, Heather; McGuirk, Joseph P.
<x xml:space="preserve">Abstract</x> In addition to cytogenetics, additional molecular markers of prognosis have been identified and incorporated into the management of patients with acute myeloid leukemia (AML). We hypothesized that rates of molecular testing would be higher in an academic center versus community sites. Rates of molecular testing in AML were higher in an academic center versus community sites in the 5 years following the World Health Organization revised classification of AML. <boxed-text content-type="graphic" id="cam4406-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>